Identification of the crosstalk among four types of adenosine‐related RNA modification in pan‐cancer. Issue 10 (14th August 2022) - Zhang, Shichao; Xiong, Yu; Wang, Weirong; Zhang, Erdong; Gu, Yan; Liu, Yang; Zeng, Zhu; Tang, Fuzhou; Ouyang, Yan
Abstract : Four types of A‐related RNA modification regulators interact with each other and even the crosstalk between the regulators could characterize the tumor immune microenvironment infiltration patterns, chemosensitivity, and cancer prognosis in patients with pan‐cancer.